Negotiating marginality: conflicts over tribal development in India - Rajakishor Mahana (Social science press, 2019)
Providing a critical ethnography of five different tribal movements fighting against the mega-industrialization projects in Odisha, India, Negotiating Marginality: Conflicts over Tribal Development in India presents a thick description of the confrontation of the tribals to the authoritative forces of state domination. This confrontation, a counter-hegemonic discourse, is neither antagonistic to change nor anti to development, but rather in fact, the author argues, that the tribals are the subaltern citizens who aspire for not only more material and economic prosperity but also freedom – freedom from domination and deprivation. The book therefore seeks to answer one important question: how do the tribals appropriate marginality in their everyday lives in challenging domination and celebrating their desires, wishes, anticipations and material prosperity as well as in coping with the ruins of frustration and suffering.